A Glimpse Into the Sexual Dimorphisms in Major Depressive Disorder Through Epigenetic Studies - Cahill, Branden; Poelker-Wells, Samuel; Prather, Jonathan F.; Li, Yun (Frontiers in Neural Circuits, 2021)
Depression is an umbrella term used to describe a mood disorder with a broad spectrum of symptoms including a persistent feeling of sadness, loss of interest, and deficits in social behavior. Epigenetic research bridges the environmental and genetic landscape and has the potential to exponentially improve our understanding of such a complex disorder. Depression is also a sexually dimorphic disorder and variations exist within epigenetic modification sites between sexes. These sex-specific mediators may impact behavioral symptomology and could serve as therapeutic targets for treatments to improve behavioral deficits. This mini review will focus on the social behavior perspective of depression and specifically explore the sexually different epigenetic modifications on depression.